2002
DOI: 10.1074/jbc.m201923200
|View full text |Cite
|
Sign up to set email alerts
|

Potassium Functionally Replaces the Second Lysine of the KMSKS Signature Sequence in Human Tyrosyl-tRNA Synthetase

Abstract: Unlike their bacterial homologues, a number of eukaryotic tyrosyl-tRNA synthetases require potassium to catalyze the aminoacylation reaction. In addition, the second lysine in the class I-specific KMSKS signature motif is absent from all known eukaryotic tyrosyl-tRNA synthetase sequences, except those of higher plants. This lysine, which is the most highly conserved residue in the class I aminoacyl-tRNA synthetase family, has been shown to interact with the pyrophosphate moiety of the ATP substrate in the Baci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…In addition, quantitatively comparing the kinetics for alanine variants at equivalent positions in the human and B. stearothermophilus tyrosyl-tRNA synthetases indicates that although the KMSKS motifs play similar roles in the two enzymes, the extent to which the KMSKS motif catalyzes the formation of tyrosyl-adenylate is significantly larger in the B. stearothermophilus enzyme than it is in the human enzyme. This is consistent with the observation that potassium appears to compensate for the absence of the second lysine in the KMSKS motif of the human tyrosyl-tRNA synthetase (19). The observation that the KMSKS motif plays a larger role in the catalytic mechanism of the B. stearothermophilus tyrosyl-tRNA synthetase suggests that inhibitors that interact with this mo- tif will have higher affinities for bacterial tyrosyl-tRNA synthetases than for their eukaryotic homologs.…”
Section: The Kmsss Sequence Catalyzes the Formation Of Tyrosyladenylasupporting
confidence: 77%
See 2 more Smart Citations
“…In addition, quantitatively comparing the kinetics for alanine variants at equivalent positions in the human and B. stearothermophilus tyrosyl-tRNA synthetases indicates that although the KMSKS motifs play similar roles in the two enzymes, the extent to which the KMSKS motif catalyzes the formation of tyrosyl-adenylate is significantly larger in the B. stearothermophilus enzyme than it is in the human enzyme. This is consistent with the observation that potassium appears to compensate for the absence of the second lysine in the KMSKS motif of the human tyrosyl-tRNA synthetase (19). The observation that the KMSKS motif plays a larger role in the catalytic mechanism of the B. stearothermophilus tyrosyl-tRNA synthetase suggests that inhibitors that interact with this mo- tif will have higher affinities for bacterial tyrosyl-tRNA synthetases than for their eukaryotic homologs.…”
Section: The Kmsss Sequence Catalyzes the Formation Of Tyrosyladenylasupporting
confidence: 77%
“…Previous investigations indicate that the loss of catalytic function by the KMSSS sequence is compensated for by the involvement of potassium in the catalytic mechanism of human tyrosyl-tRNA synthetase (19). Specifically, potassium has been shown to functionally compensate for the absence of the second lysine in the KMSSS sequence (19).…”
Section: The Kmsss Sequence Catalyzes the Formation Of Tyrosyladenylamentioning
confidence: 99%
See 1 more Smart Citation
“…The KMSKS loops of these enzymes require potassium ions for catalysis, 16 and are somewhat different from those of the bacterial TyrRSs. 17 Further analyses of the archaeal/ eukaryal TyrRSs will reveal the detailed role of the KMSKS loop.…”
Section: Induced Fit Of the Kmsks Loopmentioning
confidence: 98%
“…Structural analyses and some biochemical analyses revealed that the KMSKS loops, as well as the tRNA-recognition sites, differ between the bacterial and archaeal/ eukaryal TyrRSs. [15][16][17][18] An abundance of biochemical information is available for the bacterial TyrRSs, [6][7][8][9][10] and the L-tyrosine-bound, 4 the ATP and L-tyrosine analogue-bound 13 and the Tyr-AMP-bound 5 structures are now available. In contrast, very little data exist regarding the catalytic mechanism of the KMSKS loop in the archaeal/eukaryal TyrRSs.…”
Section: Introductionmentioning
confidence: 99%